ReVista Harvard review of Latin America. (David Rockefeller Center for Latin American Studies, 2001)
Focuses on different themes related to Latin America, Latinos/as, and the Iberian peninsula. The magazine-length publication brings together different voices on each theme, highlighting the work of Harvard faculty, students, alumni, and visiting scholars.